Document Management focused on Preventive Conservation of Documents - Paz Enrique, Luis Ernesto (2017)
The document management focused on document preservation minimizes the damages that can be generated to the institutions by the missing or loss. The study shows the aspects related to document management from the preventive conservation of documents. To obtain results, a concrete case is presented that is developed in the administrative area where large volumes of documents are stored. The objectives of the study are: 1) to diagnose the state of the documentation stored in the area of training and development, Universidad Central Marta Abreu de Las Villas, Cuba and 2) design a plan of preventive measures for documentation diagnosed. To obtain results are used methods in the theoretical and empirical levels. The funds of the institution are diagnosed, detecting environmental factors, overcrowding and mechanical physical factors that influence the conservation of collections of documents. From the results in evident the need to prioritize strategies for improving the conditions of conservation documentary in the institution, especially documents that may acquire heritage value.